Operational performance stability of grid-connected photovoltaic generator via DC–DC converter and 48-pulse voltage source inverter. (3rd April 2017) - Widyan, Mohammad S.
Abstract: This paper presents detailed steady-state stability analysis of PV generator interfaced to grid via DC–DC buck–boost converter, 48-pulse DC–AC sinusoidal Voltage Source Inverter (VSI), LC filter and transmission line. The main purpose of the DC–DC converter implementation is to inject the voltage corresponding to the Maximum Power Point of the PV generator. 48-pulse VSI is chosen as the harmonic contents in the output voltage are far away from the fundamental frequency with very small magnitudes. For numerical simulations, the complete nonlinear dynamical mathematical model in dq stationary reference frame is used including that of the terminal characteristics of the PV generator. The study comprises eigenvalues of the linearized model at various solar intensities. The robustness of the system operating point is checked by time domain simulations after small perturbations in the gird voltage and step changes on the solar insolations. Historically, series compensation of transmission lines has been used to increase the power transfer capability of the power system. In this study, the impact of equipping the transmission line with series capacitor on the system performance is highlighted. Furthermore, the effect of partial shading of the PV modules on the stability of the proposed power plant is investigated.